Listenership Sebagai Evaluasi Penerapan Konvergensi Radio - Asy'ari, Nur Aini Shofiya; Marantika, Nurhana (Jurnal Studi Komunikasi, 2020)
Previous researches on radio convergence showed that various radio stations in Ponorogo have implemented convergence by using new media platforms, such as, radio and video streaming, Youtube, and social media. However, evaluations on radio convergence has never been done before. Therefore, this research was conducted to study the effect of convergence to the listenership as well as to evaluate the implementation of radio-convergence in Ponorogo radio stations from April to July 2019. Using a survey method, the researchers administered a set of questionnaires to 267 respondents in Ponorogo to find out the listenership trends in Ponorogo community on its radio and other convergence platforms. The results of the study showed that the convergence implemented by the radios failed to raise awareness and number of radio listeners. Low awareness affects the community’s media habit. It was apparent in the fact that 84% of the respondents preferred conventional (analog) radio to a convergence platform. The results of this study also showed that convergence was unable to foster community involvement with radio. In other words, the radio was not the primary choice of the Ponorogo community in accessing information or entertainment.